Genetics Of Parkinson’s Disease - Gwazi, Amira (Libyan International Medical University Faculty of AMS, 2022)
Parkinson's disease (PD) is a neurological disease caused by loss of activity of dopaminergic neurons in substantia nigra and is characterized by presence of lewy bodies in midbrain, Symptoms exhibited as rest tremors, rigidity, bradykinesia, and posture instability. The non motor symptoms include constipation and REM sleep disorder (1,2) . Age is the biggest risk factor, and usually older adults are affected, It is a multifactorial disease with many environmental factors such as head injury well water consumption, and pesticide exposure and genetic mutations. The most important genes will be discussed in the following sections